TEKNOLOGI BLOCKCHAIN SEBAGAI ALTERNATIF TRANSAKSI DI ERA NEW NORMAL - Irawan, Bambang; Juman, Kundang Karsono; Tjahjono, Budi (Universitas Esa Unggul, 2020)
Community service activities organized by LPPM Esa Unggul University. This activity carried out by using webinars to address the current situation of the Covid-19 outbreak. This activity is a means for lecturers to share their knowledge for the development and implementation of their knowledge. Disseminating safe transactions in today's world is essential to safeguarding the health and safety of our society. Blockchain technology is an alternative to answer the current situation, without involving third parties, very high security, and successful transactions that occur. This activity provided in implementation and a very simple way how to make transactions with cryptocurrency. The results achieved in this activity can provide a clear picture of how to make transactions with blockchain technology easily and safely for daily trading activities. We hope that activities like this will continue and can be accepted by the wider community, fellow lecturers, and researchers who will later develop this knowledge for the advancement of the Indonesian nation and state.Keywords: blockchain, new normal